Comparative Analysis of SnOx Thin Films Deposited by RF Reactive Sputtering with Different SnO/Sn Target Compositions. (15th November 2017) - Kim, Cheol; Cho, Seungbum; Kim, Sungdong; Kim, Sarah Eunkyung
Abstract : A p-type oxide is a key element for transparent thin-film transistor applications. Among the various p-type oxides currently available, SnOx deposited by sputtering is the subject of interest in this study for high-performance and reliable thin films. A tin target or a tin oxide target is typically used to fabricate p-type SnOx during sputtering. A metallic target provides easy control of various film properties and chemical compositions, while a ceramic target offers structural stability and better control of stoichiometry. To use the advantages of both metallic and ceramic targets, a composite target of Sn and SnO was devised, which may provide reliable p-type SnOx and better control of structural defects. We evaluated four different composition ratios of Sn+SnO targets: a 100 mol% metallic Sn target, a composite target with 50 mol% Sn powder + 50 mol% SnO powder, a composite target with 20% Sn powder + 80 mol% SnO powder, and a 100 mol% ceramic SnO target. SnOx films were deposited under various sputtering conditions and analyzed structurally, electrically and optically. The composite target with 20 mol% Sn was found to be a promising candidate for p-type SnOx films, showing >75% transmittance and high mobility up to 9.07 cm 2 V −1 s −1 .